İSLAM HUKUKU AÇISINDAN HAYIR KURULUŞLARININ GELİR KAYNAKLARI - GÜRBÜZ, MEHMET (Fırat Üniveristesi, 2022)
Bu çalışmada hayır kuruluşlarının gelirleri ve tasarruf ilkeleri teberru akitleri bağlamında ele alınmıştır. Hayır kuruluşları aynı zamanda sivil toplum kuruluşları olarak da adlandırılıp vakıflar ve dernekler olmak üzere iki kısma ayrılmaktadır. Vakıflar mal tahsisini ifade ederken dernekler de belirli bir amaç etrafında yapılanan ve tüzel kişiliğe sahip kişi topluluklarını ifade etmektedir. Bu çalışmanın amacı fıkhu't-teberruat bağlamında hayır kuruluşlarının gelirlerini tespit etmektir. Fıkıh ve fetva literatüründen hareketle hayır kuruluşlarına yapılan teberruların sadaka hükmünde sayıldığı ve kabz sonrası teberrudan dönme imkânının kalmadığı görülmektedir. Vakıflar mütevelliler tarafından dernekler ise yönetim kurulu tarafından yönetilmektedir. Vakıfları yönetmede velâyet ve vekâlet hükümleri geçerli olurken derneklerde ise vekâlet hükümleri geçerli olmaktadır. Bu bağlamda dernek yönetim kurulu fıkhi ve kanuni açıdan vekil statüsünde kabul edilmektedir. Hayır kuruluşlarına yapılan teberrular ise şartlı ve şartsız olmak üzere iki kısma ayrılmaktadır. Vakıfların ve derneklerin yöneticilerinin şartlı bağışlarda şartlara riayetsizlikleri fıkhi açıdan tazmin sebebi sayılmaktadır. Vakıfların ya da derneklerin teberrular üzerindeki tasarrufları fıkhi olarak emanet ilkelerine göre şekillenmektedir. İslam hukukunda yed-i milke ya da yedi tazmine konu olmayan mallarda yed-i emanet ilkeleri geçerli olmaktadır. Yöneticilerin bu tür mallarda te'addî, taksir ya da ihanet sayılacak tasarrufları tazminle veya azille sonuçlanmaktadır. Fıkhi açıdan teberruların harcama yerleri kuruluşun zaruri giderleri olması; tezyîn, nakş ya da israf sayılacak bir harcama olmaması gerekmektedir. "Ra'iyye üzerinde tasarruf maslahata menû??ur" fıkhi kuralı velâyete ve vekâlete dayalı harcamaların sınırı belirleyen külli bir kaidedir. Bu bağlamda Hayır kuruluşlarına yapılan bağışlar fıkhen sadaka sayıldığından harcama alanlarının da Hanefiler açısından kurbet, maslahat ve kadr-i maruf ölçüsüne uymasının zorunlu olduğu görülmektedir.

In this study, the incomes and savings principles of charitable associations are discussed in the context of donation agreements. Associations are one of the non-governmental organizations referred to as the "Third Sector" today. Associations refer to groups of persons with legal personality which are organized around a specific purpose. The aim of this study is to determine the dispositions of associations that are subject to compensation and not, in the context of donation fiqh and to offer some suggestions. Based on the fiqh and fatwa literature, it is seen that donations made to legal entities are considered as charity (sadaqah), and there is no possibility of "recourse" from donation after dispensation. Foundations are managed by trustees, while associations are managed by the board of directors. While the provisions of custody and power of attorney are valid in managing foundations, the provisions of proxy are valid in associations. In this context, the board of directors of the association is accepted as a proxy in terms of fiqh and law. Donations made to charitable organizations are divided into two parts, conditional and unconditional. The non-compliance of the managers of foundations and associations with the conditions in conditional donations is considered as a reason for compensation in terms of fiqh. The dispositions of foundations or associations on donations are shaped according to fiqh principles. In Islamic law, the principles of yad al-amanah are valid for goods that are not subject to possessions or compensation. Dispositions of the administrators, which can be regarded as violation of right, fault and betrayal in such goods, result in compensation or dismissal. In terms of fiqh, the expenditure places of donations are the indispensable expenses of the organization; it should not be an expenditure that would be considered an ornament, embroidery or waste. The jurisprudence rule "saving over the ruled people (rayah) depends on common good (maslahah)" is a universal rule that determines the limit of expenditures based on the administration and the mandate. In this context, since donations to charitable organizations are considered charity in fiqh, it is seen that the expenditure areas must comply with the criteria of the intimacy with Allah, common good (maslahah) and at a minimum level for Hanafi Muslims.
Revenues of charities in terms of Islamic law
Keywords: Din